Haemangiopericytoma presenting with acute intracerebral haemorrhage – a case report and literature review. (May 2013) - Fredriksson, Fanny; Nordborg, Claes; Hallén, Tobias; Blomquist, Erik
Abstract Background. Intracranial haemangiopericytoma (HPC), a rare malignant tumour, should be distinguished from meningioma and solitary fibrous tumour, which have been considered as separate entities since 1993, according to histopathology and clinical characteristics. Methods. A PUBMED search for "Intracranial Haemangiopericytoma" yielded 176 articles, where 26 were of particular interest for this review article. Case report. Our patient, a 27-year-old man with HPC of grade III according to WHO, presents with an acute intracerebral haematoma, which is extremely rare. Results. Surgery (total resection) is the primary treatment. Long-term close clinical and radiological follow-up is crucial due to the high rate of recurrence and tendency for development of metastasis. Discussion. The effects of postoperative radiotherapy need further investigation. Besides neurosurgery, radiotherapy should always be considered in both patients with these highly malignant tumours (WHO grade III) and in patients with partial resection or inoperable cases (WHO grade II).